Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13054-019-2399-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine clearance with CytoSorb® during cardiac surgery: a pilot randomized controlled trial

Abstract: Background Cardiopulmonary bypass (CPB) is often associated with degrees of complex inflammatory response mediated by various cytokines. This response can, in severe cases, lead to systemic hypotension and organ dysfunction. Cytokine removal might therefore improve outcomes of patients undergoing cardiac surgery. CytoSorb® (Cytosorbents, NJ, USA) is a recent device designed to remove cytokine from the blood using haemoadsorption (HA). This trial aims to evaluate the potential of CytoSorb® to decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 20 publications
(22 reference statements)
12
107
0
1
Order By: Relevance
“…e results of our trial are supported by two prospective randomized clinical trials, by Bernardi et al [23] (on 37 patients, 18 with hemadsorption) and by Poli et al [25] (on 30 patients, 15 with hemadsorption). Both showed no effects of hemadsorption with Cytosorb ® during CPB, neither on 'biochemical alleviation' of post-CPB SIRS, nor on patient clinical outcomes.…”
Section: Discussionsupporting
confidence: 73%
“…e results of our trial are supported by two prospective randomized clinical trials, by Bernardi et al [23] (on 37 patients, 18 with hemadsorption) and by Poli et al [25] (on 30 patients, 15 with hemadsorption). Both showed no effects of hemadsorption with Cytosorb ® during CPB, neither on 'biochemical alleviation' of post-CPB SIRS, nor on patient clinical outcomes.…”
Section: Discussionsupporting
confidence: 73%
“…The case series comparing intraoperative vs. intraoperative and postoperative use of Cytosorb showed that more intense therapy (intra-operative and post-operative) might be associated with patient improvement [27]. However, two prospective, randomized, blind and controlled trials did not confirm the previous results [28,29]. There was no significant difference in inflammatory markers, blood substitution, vasopressor need or mortality.…”
Section: State Of Knowledgementioning
confidence: 94%
“…The listed exclusion criteria are set to minimize the impact of perioperative variables, which may potentially undermine the validity of the study. The exclusion criteria are also backed up by a number of studies focusing on cardiac surgery [ 13 15 ].…”
Section: Methodsmentioning
confidence: 99%